Comparison of Single Layer Interrupted Extramucosal Anastomsis with Double Layer Continuous Anastomosis Among Patients with Benign Small Intestinal Pathology (Journal of Fatima Jinnah Medical University, 2018)
Objective: To compare outcome of single layer interrupted extramucosal anastomsis with double layer continuous anastomosis among patients with benign small intestinal pathology such as perforation, tuberculosis, trauma or typhoid.Methodology: This prospective randomized controlled trial was conducted at Surgical floor LGH/PGMI. The study was completed in six months using non-probability consecutive sampling. Two hundred patients with benign intestinal pathology requiring intestinal anastomosis were divided in two groups, 100 patients in each group were taken in group A patients were managed with single layer extramucosal interrupted anastomosis and in group B patients were treated with underwent double layer continuous anastomosis. Variable like leakage was described by frequency distribution table, Chi-square test was applied as a test for significance & p-value ≤ 0.05 was considered significant.Results: Five (5%) patients in group A had leakage detected on seventh day, while 15 (15%) patients in group B had leakage detected on seventh day. No leakage was seen among 95 (95%) and 85 (85%) patient in group A and B, respectively. (p = 0.018)Conclusions: Less leakage occurred with single layer anastomosis as compared with double layer anastomosis. Hence we recommend that single layer anastomosis should be adopted for patients with benign intestinal intestinal pathologies.
Keywords: Single layer interrupted anastomosis; double layer continuous anastomosis; leakage; intestinal pathologies